Governance in a Global Economy : Political Authority in Transition - Lake, David A., 1956-; Kahler, Miles, 1949- (Book collections on Project MUSE., 2003)
Critics of globalization claim that economic integration drains political authority from states: devolving authority to newly empowered regions, delegating it to supranational organizations, and transferring it to multinational firms and nongovernmental organizations. Globalization is also attacked for forcing convergence of state institutions and policies and threatening the ability of societies to chart their own democratically determined courses. In Governance in a Global Economy, Miles Kahler and David Lake assemble the contributions of seventeen leading scholars who have systematically investigated how global economic integration produces changes of governance. These authors conclude that globalization has created a new and intricate fabric of governance, but one that fails to match the stark portrait of beleaguered states. Exploring changes in governance across several policy areas (such as tourism, trade, finance, and fiscal and monetary policy), the authors demonstrate that globalization changes the policy preferences of some actors, increases the bargaining power of others, and opens new institutional options for yet others. By reintroducing agency and choice into our understanding of globalization, this book provides important new insights into the complex and contingent effects of globalization on political authority and governance. The introduction and the conclusion are by the editors the contributors are James A. Caporaso, Benjamin J. Cohen, Barry Eichengreen, Zachary Elkins, Geoffrey Garrett, Peter Gourevitch, Virginia Haufler, Michael J. Hiscox, Robert O. Keohane, Lisa L. Martin, Walter Mattli, Kathleen R. McNamara, Joseph S. Nye, Jr., Jonathan Rodden, Ronald Rogowski, Beth A. Simmons, and Peter Van Houten.